HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP PEMBERIAN ASI EKSLUSIF DI POSYANDU LUMASEBU - Sahriyani; Aris Prastyoningsih; Tresia Umarianti (Jurnal Medicare, 2025)
Breast milk is a white liquid produced by a woman's mammary glands and given through the breastfeeding process. Based on an initial survey conducted in the working area of Alusi Community Health Center, out of 10 respondents given a questionnaire, 7 did not provide exclusive breastfeeding, while 3 did. Among them, 4 had low knowledge, 3 had moderate knowledge, and 3 had good knowledge. Additionally, 6 respondents had a negative attitude, while 4 had a positive attitude. The purpose of this study is to determine the relationship between mothers' knowledge and attitudes toward exclusive breastfeeding at the Lumasebu Posyandu. This study employs a correlational analytic research design. The study population consists of all mothers with infants aged 6–24 months at Lumasebu Posyandu from November to December 2024, totaling 30 participants, using a saturated sampling method. The independent variables in this study are knowledge and attitude, while the dependent variable is exclusive breastfeeding. The data used include both primary and secondary data. The study applies the Spearman Rank correlation analysis. The findings show that knowledge has a p-value of 0.008, leading to the rejection of Ho (p < 0.05), indicating a significant relationship between knowledge and exclusive breastfeeding. Attitude has a p-value of 0.005 (< 0.05), meaning there is a significant relationship between mothers' attitudes and exclusive breastfeeding. The independent variable with the highest OR value is attitude, with an OR of 8.224, indicating that attitude is the dominant factor influencing exclusive breastfeeding.